Sine totoo 2006 : the best of GMA's serbisyong totoo - GMA (Quezon City : Felta Multi-media, 2006)
Contents : 1. Pinoy tapat ka ba? / Mike Enriquez.-- 2. Maka-hayop / Maki Pulido.-- 3. Abakada ni inay / Rhea Santos.-- 4. Pagpag / Arnold Clavio.-- 5. The good samaritans / Vicky Morales.
Keywords: Documentary